A Study of the CO Sensing Responses of Cu-, Pt- and Pd-Activated SnO2 Sensors: Effect of Precipitation Agents, Dopants and Doping Methods - Venkata Krishna Karthik Tangirala; Heberto Gómez-Pozos; Ventura Rodríguez-Lugo; María De La Luz Olvera (Sensors, 2017)
In this work, we report the synthesis of Cu, Pt and Pd doped SnO2 powders and a comparative study of their CO gas sensing performance. Dopants were incorporated into SnO2 nanostructures using chemical and impregnation methods by using urea and ammonia as precipitation agents. The synthesized samples were characterized using X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HR-TEM). The presence of dopants within the SnO2 nanostructures was evidenced from the HR-TEM results. Powders doped utilizing chemical methods with urea as precipitation agent presented higher sensing responses compared to the other forms, which is due to the formation of uniform and homogeneous particles resulting from the temperature-assisted synthesis. The particle sizes of doped SnO2 nanostructures were in the range of 40–100 nm. An enhanced sensing response around 1783 was achieved with Cu-doped SnO2 when compared with two other dopants i.e., Pt (1200) and Pd:SnO2 (502). The high sensing response of Cu:SnO2 is due to formation of CuO and its excellent association and dissociation with adsorbed atmospheric oxygen in the presence of CO at the sensor operation temperature, which results in high conductance. Cu:SnO2 may thus be an alternative and cost effective sensor for industrial applications.